Analisis Kerentanan Sistem Irigasi dengan Indeks Kelentingan di Daerah Irigasi Wilayah Daerah Aliran Sungai Brantas - Wahyuni Setyo Lestari; Didik Suprayogo; Sugeng Prijono (agriTECH, 2018)
The aim of study was to explore the vulnerability of an irrigation system due to climate change by using a resilience index in irrigation areas (D.I.) of Brantas watershed (Molek, Jatikulon, Menturus, and Konto). There were eighty-two water-user farmers’ associations (HIPPA), sixty eight of them were selected as survey targets. The Duckstein and Plate formula was applied to calculate the resilience index of an irrigation area, while the multinomial regression was used to identify the dominant factors of resilience index. This study proved that Molek, Jatikulon, Menturus and Konto irrigation areas (D.I.) were impacted by climate change with different scales of resilience. The resilience index was 100% for Molek Irrigation area, 80% for Jatikulon irrigation area, 50% for Menturus irrigation area, and 33% for Konto irrigation area. Climate change was predicted to cause a decrease of harvested area, in such a way that in the condition of El Niño around 48% in Konto Irrigation Area, 34% in the Menturus Irrigation Area, 28% at the Jatikulon Irrigation Area, and 15% in the Molek Irrigation areas. Nevertheless, in the La-Nina condition, there was no increase of harvested area in the entire irrigation area studied, even, there was a 28% decrease of harvested area in Konto irrigation area, and 6% in Menturus irrigation area. The most powerful threat toward an irrigation system’s sustainability was the environment, followed by physical, social, and economic aspects respectively. The results of this study implicate to the improvement of irrigation management policy, namely to the operational pattern of irrigation system, which uses a resilience index (Ik) as basic measure of irrigation system management out of the K-factor.